An Accurate Evaluation of Consumption Pattern in Reconfiguration of Electrical Energy Distribution Systems - Mahdavi, Meisam [UNESP]; Javadi, Mohammad; Wang, Fei; Catalao, Joao P. S. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Electrical energy consumption pattern has always been important for power distribution companies, because load variations and method of electricity consumption affect energy losses amount. For this, distribution companies frequently encourage the network users to correct their energy consumption behavior by suggesting some incentives. Reconfiguration of distribution systems for a specific load pattern is an effective way to reduce the losses. Hence, some papers have considered load variations in distribution system reconfiguration (DSR) to show importance of consumption pattern for reconfiguration decisions. However, most of specialized studies have been ignored load changes in their reconfiguration models because of a significant increase in computational burden and processing time. On the other hand, neglecting the consumption pattern causes the energy losses is calculated inaccurately. Therefore, this paper intends to evaluate effect of load pattern on reconfiguration plans in order to find out importance of considering load variations in energy losses minimization via DSR. The analysis has been conducted on well-known distribution systems by AMPL (a classic optimization tool).
Keywords: Consumption pattern; Distribution networks; DSR; Energy losses